(3GdJbQjQGJs - (3Ydj GdQhROQj, J (B1290 (3g`s ((3eYjf GdOjf CMeO Hf QLH Ydjs)
(3ChdgG (B:s
(3ds
(3JHUQI GdYfhGf (B:s
(3JbQjQGJ GdCUhds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdPQjYI; HQbe(B: 1662s
(3GdPQjYI; HQbe(B: 1662s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3CUhd Gdabgs